A Multidimensional Analysis of Pilgrimage: Social, Economic, and Religious Authority in the Mbah Priok Grave Pilgrimage - Siti Khotijah; Farida Novita Rahmah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This article aims to examine the pilgrimage to Mbah Priok’s grave from social, economic, and religious perspectives. This qualitative research employs a combination of literature review, historical analysis, and anthropological methods. The study reveals that the Tomb of Mbah Priok, also known as Habib Hasan Al Hadad, serves as a significant pilgrimage site despite historical controversies. The Al Hadad family has maintained religious authority and withstood temporal challenges. Notably, in April 2010, the Al Hadad family engaged in a physical and administrative conflict with a company expanding the area. During Governor Ahok’s tenure, the tomb was designated a religious tourism site and cultural heritage, fostering economic growth for local businesses and the surrounding community. This research contributes to understanding the socio-economic and religious dynamics of pilgrimage sites, highlighting the complex interplay between tradition and modernity